Biochar Derived from Domestic Sewage Sludge: Influence of Temperature Pyrolysis on Biochars’ Chemical Properties and Phytotoxicity - Rahma Inès Zoghlami; Sarra Hechmi; Rihab Weghlani; Naceur Jedidi; Mohamed Moussa (Journal of Chemistry)
The pyrolytic conversion of domestic sewage sludge (SS) into biochar is a promising method to reduce its large volume and recycle its high-value fuel gas as renewable energy and the use of its chemicals as soil fertilizers. Even though the effects of pyrolysis temperature on energy recovery have been extensively studied, little information has been found on nutrient recovery and biochar’s phytotoxicity before its reuse as a soil amendment. This study aims to investigate the ideal pyrolysis temperature that guarantees higher fertility levels as well as meeting quality standards for land disposal. Accordingly, air-dried domestic sewage sludge has been pyrolyzed at 260°C (PSS1), at 420°C (PSS2), and at 610°C (PSS3) with a residence time of 20, 40, and 60 minutes, respectively. The raw sewage sludge and the produced biochars have been analyzed to determine their volatile organic matter (VOM), mineral content (MC), nutrients’ level (total nitrogen TN, available phosphorus P, and potassium K), alkalinity (pH), and salinity (electrical conductivity EC and Na). The toxic effect of biochars derived from SS has been evaluated through the analysis of trace metals (Pb, Cr, Cd, Cu, and Zn) and their toxicity by measuring root elongation inhibition (REI). As expected, pyrolysis temperature has a significant impact on the biochars’ characteristics. This has been justified by higher VOM, TN, and P in the sewage sludge (SS) and the biochar (PSS1) produced at low temperature (260°C). However, higher pH, EC, Na, and K have been found in the biochars (PSS2 and PSS3) produced at higher temperature (420 and 610°C). The effect of pyrolysis temperature on trace metals concentrations has shown different patterns from one element to another, which indicates lower levels in the biochar (PSS2) produced at 420°C. As a result, the lowest REI has been observed in PSS2 compared to that in SS, PSS1, and PSS3, which highlights that 420°C is the ideal pyrolysis temperature for the safe reuse of SS as a soil amendment.